Mid-term comparison of highly porous versus hydroxyapatite-coated porous surface in the same cup system: a retrospective single-center study - Tetsuya Tachibana; Hiroki Katagiri; Kazumasa Miyatake; Takahisa Ogawa; Masanobu Hirao; Ryohei Takada; Ryusuke Saito; Tetsuya Jinno (BMC Musculoskeletal Disorders)
Abstract Background In this study, we aimed to compare the mid-term clinical and radiographic outcomes of highly porous and hydroxyapatite (HA)-coated porous titanium cups using the same cementless cup system in patients undergoing total hip arthroplasty (THA). We investigated the differences in radiolucent line (RLL) formation, cup migration, and clinical outcomes between the two surface processing methods. Methods This retrospective study included 209 hips (116 in the highly porous group and 93 in the HA porous group) with a minimum follow-up period of over 4 years. Using standardized anteroposterior pelvic radiographs, we conducted radiographic evaluations to assess cup orientation, initial gaps, and RLLs. Migration was analyzed using Einzel-Bild-Rontgen Analysis (EBRA), focusing on a subset of 28 randomly selected cups from each group as determined by power analysis. Clinical outcomes were measured using the Japanese Orthopedic Association (JOA) hip score. The primary outcome was the incidence of cup revision, and the secondary outcomes were postoperative JOA scores and the incidence of initial gaps and RLLs. Results No cup revisions were made in either group. Both groups had significant postoperative improvements in the JOA scores, with no differences observed during the follow-up period. At baseline, the initial gaps were observed at similar rates (highly porous vs. HA porous [51% vs. 52%]; p = 0.97). However, at the 5-year follow-up, the initial gaps were resolved in nearly all cases. In the highly porous group, RLLs were significantly more frequent during the first-year follow-up (23% vs. 2%; p < 0.0001). However, they decreased in all cases, and none of them exhibited RLL expansion. EBRA migration analysis revealed no significant differences between the groups. Conclusion Both groups demonstrated comparable mid-term clinical and radiographic outcomes. The highly porous group exhibited higher initial RLL incidences. However, RLL diminished over time without compromising the migration or clinical results. Both designs are reliable options for cementless THA.